BALANCE OF PROGRESS AND REGRESS IN THE DEVELOPMENT OF POST-INDUSTRIAL SOCIETY - A. A. Kumpen; M. N. Rosenko (Дискурс)
Maintenance of progress and regress of social systems in different historical context is considered in the article. Being interdependent directions of movement, progress and regress can be considered as integral indicators of society viability and possibility of its further development. Correlation of progressive and regressive changes in post-industrial society is defined by transformation of the globalized world civilization including heterogeneous types of socio-political systems. Modern social realities demonstrate continuous interrelation of the progressive development with a regressive vector that defines changes of public relations. This difficult multi-aspect historical process covers all spheres of post-industrial society, including its structural organization, level of stability of social system, character of internal and external contradictions.